Development of Instant Nutritious Beverage from Germinated Jasmine Brown Rice for Elderly Consumers - Duangjongkon Sutinium; Vichai Haruthaithasan; Penkwan Chompreeda (Agriculture and Natural Resources, 2008)
A rise in the number of elderly consumers (age 60+) will drive the need for healthy, convenience and good taste foods. Germinated brown rice provides good source of nutrients especially dietary fiber and γ-aminobutyric acid (GABA). Thus, the objective of this study was to develop instant nutritious beverage from germinated jasmine brown rice (GJBR) as a new choice of healthy drink for elderly consumers. An optimum formulation of instant nutritious beverage from GJBR was formulated by using linear programming to minimize cost and energy and maximize protein and dietary fiber. Cooked GJBR flour was prepared by steaming GJBR, removing husk, cooking, drying and grinding. Cooked GJBR flour (150 mesh) 100 grams contained protein 9.03 grams and dietary fiber 3.52 grams. According to survey study, the important factors which elderly consumers used for selection the instant beverage were nutritive value, good taste and convenience to use. The optimal formulation of the instant beverage from GJBR consisted of 20% cooked GJBR flour, 20% sugar, 44.6% skim milk powder, 5.1% vanilla powder, and 10% inulin. Premixed of vitamin B6, vitamin B12, folic acid and L-Carnitine was added to the instant beverage. One serving (35g) of the instant beverage composed of energy 120 Kcal, protein 5.64 g, dietary fiber 3.72 g, carbohydrate 24 g, fat 0.18 g, vitamin B6 1 mg, vitamin B12 0.82 μg, folic acid 59.3 μg and calcium 203 mg. The water activity of the product was 0.28. All of 50 elderly consumers that tested product accepted the product. If the product available in the market, 80% of them decided to purchase this product at the price equal to commercial ones after they had learned about the nutritional quality of the instant GJBR beverage.